Estimación de la fragilidad para yacimientos en roca generadora mediante registros de pozo en las formaciones la Luna y Cogollo, Cuenca de Catatumbo, Colombia (2020)
Geomechanics is a fundamental component in the study of unconventional reservoirs in source rock, given that the production of this type of reservoir depends on the implementation of multi-stage hydraulic fracturing operations, brittleness is an important geomechanical parameter for the preliminary evaluation of these reservoirs, as it helps to differentiate the sections that present a brittle behavior from a ductile one. In the world there are a large number of source rock reservoirs; The United States, China and Argentina have stood out for the exploitation of this type of reservoir, which has allowed the development of multiple studies for the evaluation of parameters such as mineralogical Brittleness Index. In the United States, in the Barnett, Eagle Ford and Woodford formations, models were implemented that include the creation of statistical correlations from linear regressions in graphs of mineralogical Brittleness with compressional sonic slowness or mineralogical Brittleness with Neutron Porosity Log. this to allow a calculation of the mineralogical Brittleness index through well logs.